Melatonin-Hydrogel Delivery Systems for Effective Treatments of Periodontitis: Translational Perspectives from Material Designs to Clinical Applications - Ting Liu; Li Zhang; Qiong Zhang; Qitao Zhao; Sisi Gou; Yifo Liu; Run Zhong; Guowei Mao; Hao-Ying Li (Gels, 2026)
Periodontitis is a chronic infectious disease characterized by progressive destruction of periodontal supporting tissues. Conventional treatments, including mechanical therapy and local drug delivery, are hindered by poor drug retention, burst release, and short duration of action. Melatonin (MT), an endogenous indoleamine, exhibits multi-target protective effects on periodontal tissues via reactive oxygen species scavenging, inflammatory regulation, bone metabolism balance, and microecological modulation; however, its clinical application is severely limited by a short half-life and rapid local clearance. To address these issues, hydrogels have been explored as carriers for periodontal drug delivery. These hydrophilic polymers offer biocompatibility, strong tissue adhesion, and sustained release properties, thereby enhancing local delivery and therapeutic outcomes. MT-hydrogel systems enable synergistic effects by integrating the modifiable functions of hydrogels with the pharmacological activities of MT. Their cooperative therapeutic mechanisms are critically categorized as antioxidant, anti-inflammatory, pro-regenerative, and microecological regulatory. This review summarizes key formulation determinants, including substrate selection, drug loading/sustained-release strategies, and functional modifications, and compiles recent data from in vitro, in vivo, and preliminary clinical studies. Furthermore, critical challenges in clinical translation are analyzed, and future research directions regarding formulation optimization and clinical application are proposed, providing a theoretical foundation for the development of effective MT-hydrogel systems for periodontitis therapy.